The gut microbiota regulates acute foreign body reaction and tissue repair after biomaterial implantation. (October 2022) - Chen, Sheng-Lun; Lundy, David J.; Ruan, Shu-Chian; Chen, Hung-Chih; Chao, Yu-Kai; Cheng, Yuan-Yuan; Prajnamitra, Ray Putra; Liao, Chun-Chieh; Lin, Chung-Yen; Lai, James J.; Hsieh, Patrick C.H.
Abstract: We hypothesized that the host microbiome may influence foreign body responses following biomaterial implantation. To test this, we implanted a variety of clinically relevant biomaterials into germ-free or antibiotic-treated mice. Surprisingly, these mice displayed less fibrous tissue deposition, reduced host cell recruitment to the implant site, and differential expression of angiogenic and inflammatory markers. These observations were reversed upon fecal microbiome reconstitution, confirming a causal role of the host microbiome. In a clinically relevant disease model, microbiome-depleted mice cleared hyaluronic acid and bone marrow mononuclear cells from ischemic hind limb tissues more slowly, resulting in an improved therapeutic response. Findings were confirmed in pigs which showed reduced fibrotic responses to a variety of implanted materials. Lastly, we profiled changes in the host microbiome following material implantation, implicating several key bacteria phyla.